Two Results on Infinite Transversal Theory (MATEMATIKA, 2013)
By the assistance of an independence space on a set S with finite rank, this paper presents a way to determine a family of subsets of S to possess an independent transversal. Afterwards, it provides another result on infinite transversal relative to partial transversals of a family of subsets of S. The two results are in the field of transversal theory. Keywords: transversal; independence space; finite rank; finite partial transversal. 2010 Mathematics Subject Classification: 05B35; 52A35